(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
This research about the effectiveness of four baits to control rats, Sigmodon perruvianus and Peromyscus maniculatus species; in sugarcane crop (Saccharum officinarum), Ragnar and Ecu-01 varieties, was held at the Sugarmill La Troncal, Cañar Province, Ecuador, on a plantation established at the age of seven months. The research to determine which of these varieties rodents prefer and measure the effectiveness of the four baits to control rats based on the bulkiness of bait that the rats consume. After the test is finished we can concluded that the rodents prefer the Ecu-01 variety than Ragnar variety. The baits with the highest consumption were Champion + corn; Ultra Plus, and then Klerat, while Champion + peanut bait had the least attention by the rats, since it takes more time to consume it. On the second day of trapping the rats eat more bait, because in the following days the trend decreases. A remarkable effect in rodent control is evident within two weeks of the baits been applied, because they have a slow but effective action.